Stability Study in Dielectric Ring Loaded Periodic Interaction Structure for a Megawatt Class Gyrotwystron - Signh A.S.; Thottappan M. (My University, 2025)
In this paper, the stability and design studies of an X-band gyrotwystron using a distributed loss technique at its output waveguide section are presented. The periodic dielectric loading (PDL) in the output section of the amplifier suppresses the self-generated backward-wave parasites including TE11, TE21, and second harmonic TE02 modes. These parasites are investigated using the small-signal linear theory. The PDL technique improves not only the stability of the amplifier but also its gain. The PDL waveguide provides a transmission loss of 0.63 dB/cm to the desired TE01 operating mode at 10 GHz that is good enough to stabilize the operation of gyrotwystron against parasites. The nonlinear simulation predicted an RF output power of ∼25 MW in the TE01 mode for the dc beam of 220 A, 440 kV. © 2018 IEEE.